(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2020)
The objective of the present paper is to evaluate the turbulent flow around the Ahmed body immersed in air and to determine its aerodynamic coefficients for different slant angles. The bidimensional non-stationary analysis of an incompressible flow around the Ahmed body is carried out for three different rear angles which are 0°, 10° and 25°. The numerical simulations were performed under the same Reynolds number, Rel = 94 000, based on the free streamwise velocity, uâˆž, the longitudinal length of the Ahmed body, l, and the kinematic viscosity of the work fluid, Î½. The additional diffusivity caused by the turbulent motion was approached using the Boussinesq’s idea through the k-Ï‰ SST. In the paper, aerodynamic coefficients of drag and the pressure and velocity fields are presented to characterize the Ahmed body for such slant angles, as well as the flow detachment point, determined through the dimensionless skin friction factor distribution on the body’s surface. Numerical simulations were compared with available results in open literature and showed agreement with other authors. The drag coefficient in the body with slant angle of 25° was found to matches with the drag coefficient equation proposed by Bello-Millán et al. (2016) as a function of Reynolds number.